2017
DOI: 10.1002/hec.3495
|View full text |Cite
|
Sign up to set email alerts
|

Population health and the economy: Mortality and the Great Recession in Europe

Abstract: We analyze the evolution of mortality-based health indicators in 27 European countries before and after the start of the Great Recession. We find that in the countries where the crisis has been particularly severe, mortality reductions in 2007-2010 were considerably bigger than in 2004-2007. Panel models adjusted for space-invariant and time-invariant factors show that an increase of 1 percentage point in the national unemployment rate is associated with a reduction of 0.5% (p < .001) in the rate of age-adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 93 publications
(133 reference statements)
5
77
0
Order By: Relevance
“…25 However, the evidence around the impact of economic recession on health and mortality of populations, rather than individuals, is complex and contested. 26 The response to this financial crisis, across many countries, was to implement a range of austerity policies whereby public spending was reduced in the pursuit of balanced budgets. As a result many public services experienced substantial reductions in their budgets and public sector wages and income transfers to lower income groups were frequently reduced in real terms.…”
Section: Meaningexplanations and Implicationsmentioning
confidence: 99%
“…25 However, the evidence around the impact of economic recession on health and mortality of populations, rather than individuals, is complex and contested. 26 The response to this financial crisis, across many countries, was to implement a range of austerity policies whereby public spending was reduced in the pursuit of balanced budgets. As a result many public services experienced substantial reductions in their budgets and public sector wages and income transfers to lower income groups were frequently reduced in real terms.…”
Section: Meaningexplanations and Implicationsmentioning
confidence: 99%
“…In 2015, COPD was associated with 241.4 years of life lost among 100 000 individuals (all sexes), which was, however, considerably lower than the national average [63]. Additionally, a recent Greek study has reported that mortality from respiratory diseases has declined during the crisis, in contrast with its increasing trend before [64]. However, conflicting studies have indicated that economic downturns are historically associated with increases in mortality, mainly attributable to psychosocial stress due to unemployment [65] or intentional violence [6].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…Much existing research has focused on the relationship between the economic downturn, rises in unemployment and worsening mental health outcomes 3 4. Mirroring historical trends, in the aftermath of the recession there was an improvement in all-cause mortality across Europe,5 paradoxically accompanied by a sharp rise in suicide rates which disproportionately impacted men 6…”
Section: Introductionmentioning
confidence: 99%